OPTIMALISASI PERLINDUNGAN DAN BANTUAN HUKUM PEKERJA MIGRAN MELALUI PROMOSI KONVENSI PEKERJA MIGRAN TAHUN 2000 - Krustiyati, Atik (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Enforcement of legal protection and aid for Indonesian Migrant Worker (TKI) still facing a lot of obtacles from many factors, including substance, structure, and culture of law. Ratification of Migrant Worker Convention in Act No. 6 / 2012 and ratification of International Convention of Civil and Political Rights (ICCPR) into Act no.12/ 2005 must be seen as one of state responsibility in extending legal protection and aid for migrant worker. Implementation of these two Convention are immediately and justiciable in nature, since Act No. 16/ 2011 regarding Legal Aid has been previously implemented by Indonesian Government. Adoption of Migrant Worker Convention and ICCPR into national legal system must be accompanied by implementation of legal instruments consistently and continuously regardless of legal, procedural, or administrative. Implementation of this law is necessary to optimally enforce all resources to settle any problems arise regarding migrant workers. Government must keep working on the Revision of Act No. 39 2004 and harmonization between international legal instrument with national legal instrument. Key words : Protection of law, legal aid, migrant worker